ANALISIS KEMAMPUAN MULTI REPRESENTASI PESERTA DIDIK PADA MATERI USAHA DI MADRASAH ALIYAH - Rizki Murniati; Edy Tandililing; Muhammad Musa Syarif Hidayatullah (Universitas Tanjungpura, Prodi Pendidikan Fisika, 2021)
The purpose of this study to identify student's multi-representation ability about work at MA Negeri Bengkayang. The method used is the survey method without comparative group which is descriptive correlative with research instrument in the form of descriptive test on the multi-representation ability test of five questions and multiple-choice test on the learning outcomes test often questions. the validity of the multi-representation test was 3.45 whit valid criteria and the validity of the learning outcomes test was 3.52 with valid criteria Meanwhile, the reliability of the multi-representation test was 0.516 in the sufficient category and the reliability of the learning outcomes test was 0.55 in the sufficient category. The study found that the multi-representation ability of students was low with an average percentage of 33.08%. The multi-representation ability of students with the highest percentage is in the image to symbol representation type, which is 75%, while the multi-representation ability of students with the lowest percentage is in the verbal to mathematical representation type, which is 5.19%. This study also did not found a correlation (r count 0.04 > r table 0.4848) between multi-representation ability and student's learning outcomes. The result of this study is expected to be taken into consideration in determining learning strategies.